The Impact of Military Spending Cutbacks on Economic Activity in an Incentive-Wage Two-Sector Aggregative Economy - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 1996)
We examine the theoretical outcomes of disarmament on economic activity in a two‐sector model of endogenous equilibrium unemployment rate. Three main shocks are analyzed: Exogenous cutbacks in military spending on the capital good and employment, and a reduction in public sector debt. The first shock is contractionary for equilibrium employment if the capital‐goods producing sector is relatively labour‐intensive but expansionary under the alternative factor intensity assumption. The second shock is contractionary for employment under either relative factor intensity assumption. If Ricardian equivalence fails, a reduction in public sector debt is likely to expand long‐term employment (JEL E24).